Conceptual aspects of methodology developing for integral service intelligent digital networks - Жуков, И. А.; Ластовченко, М. М. (Problems of Informatization and Control, 2009)
Instrumental-technological complex (ITC) for intelligent engineering and design high bandwidth digital networks of integration service building and development problem is considered with requirements to ITC and its base components substantiation